Reevaluation of Rhipidomys emiliae (J.A. Allen 1916) and description of a new Rhipidomys (Rodentia: Cricetidae) species from Amazonia and Cerrado - Lanes, Rayque De Oliveira; Bonvicino, Cibele Rodrigues (Zootaxa, 2023)
We present the revalidation of the sigmodontinae rodent species R. emiliae, as well as the description of a new species for the genus Rhipidomys. The maximum likelihood analysis recovers R. emiliae as sister species of the clade with Rhipidomys sp. nov. and R. ipukensis, with high bootstrap values. Comparisons between these species based on the external, cranial, and dental morphology identified several unique characters in Rhipidomys sp. nov., including more grayish brown color of the dorsal coat, subsquamosal fenestra wide and long, angular process ends in the same position of the end of condyloid process, conspicuous protostyle and enterostyle. We describe a new karyotype (2n = 44 and FN = 64) for the genus and, based on an integrative analysis together with morphology and molecular phylogeny, assign it to R. emiliae, and assign the karyotype with 2n = 44 and FN = 52 to Rhipidomys sp. nov.. The analysis integrating data indicated that R. emiliae has a geographic distribution restricted to the lowlands of eastern Amazonia, whereas Rhipidomys sp. nov. occurs in the central Amazonia and Cerrado. The data showed that some Rhipidomys species have its distribution currently limited by rivers, as Rhipidomys sp. nov. occurring west of the Araguaia-Tocantins interfluve, R. emiliae east of the Tocantins River, and R. ipukensis between the Tocantins and Araguaia rivers. This work, in addition to revealing a still unknown biodiversity describing a species, brings a new understanding to the genus, and shows how integrating different markers helps in the correct association between the nominal form and the karyotype.